Investigating the phenology of juvenile potamodromous brown trout (Salmo trutta L.) in two large lake catchments. Issue 3 (5th January 2022) - Kennedy, Richard J.; Rosell, Robert; Allen, Michelle
Abstract: There is growing interest in the phenology of juvenile Salmo trutta and evidence of significant downstream migration during the autumn in some anadromous populations. The present study used acoustic telemetry to examine the phenology of potamodromous trout parr across a region encompassing two large lake catchments. One hundred sixty‐seven trout parr were tagged in late summer across four lake tributaries between 2018 and 2020. In total, 75 tagged parr migrated into the lakes with 67 (89%) migrating between September and December and 8 (11%) migrating between March and June. Autumn migration was highly prevalent across all the tributaries, with 16%–66% of each tagged sample exhibiting autumn migration, and 0%–15% of each tagged sample exhibiting spring migration. Autumn migrants were significantly longer and heavier than spring migrants, but condition factor was similar. Autumn migrants were associated with higher river discharge levels and lower water temperatures than spring migrants. The management challenges posed by extensive autumn migration behaviour in migratory trout stocks are examined and discussed.